To Cultivate Creativity and a Maker Mindset Through an Internet-of-Things Programming Course - Jeng, Yu-Lin; Lai, Chin-Feng; Huang, Sheng-Bo; Chiu, Po-Sheng; Zhong, Hua-Xu (Frontiers in Psychology, 2020)
With the swift development of technology in recent years, entrepreneurs are facing rapid changes in industry. To cope with such changes at home and abroad, The Ministry of Education is actively promoting innovative education with the aim of cultivating students' entrepreneurship. On this basis, this study proposes an innovative curriculum design based on an Internet-of-Things (IoT) programming course. The reason is that it develops computational thinking skills while students are learning programming and also cultivates logical thinking skills and problem-solving skills, which are critical to entrepreneurship. We also design a number of learning activities that enable students to express their opinions and ideas while gaining more knowledge through peer interaction and discussion. Overall, this study explores the impact of "maker education" on students' attitudes towards computer thinking. The results indicate that maker education has a positive impact on their ability to learn computer skills. In terms of learning motivation, students are not motivated by maker education and reduce their confidence on the curriculum. The reason may be that the curriculum requires the acquisition of software and hardware skills, which will increase the student's learning burden, so they more likely to encounter learning disabilities.